Investigações sobre estímulos com significado e formação de classes de equivalência entre estímulos - Marin, Ramon (Universidade Federal de São Carlos, 2024)
The stimulus equivalence paradigm, as a model of meaning, allows for inferences about the learning of equivalent stimulus classes under everyday contingencies and hypothesizes that any meaningful stimulus must be a member of a class. With the general aim of developing preparations to experimentally assess pre-experimental relations between stimuli, this study conducted four experiments that empirically investigated (a) the possibility of identifying pre-experimental relations between stimuli through categorization tasks (sorting, Experiment 1), (b) the effect of contextual cues in tasks that seek to identify relations between stimuli that were not experimentally learned (Experiment 2), (c) the effect of teaching procedures on categorization responses when stimuli with pre-experimental meaning are used in tasks (Experiment 3), and (d) the learning of arbitrary relations between stimuli and the formation of equivalence classes through progressive exposure to teaching tasks alternated with probes to assess the emergence of non-directly taught relations (Experiment 4). In Experiments 1 and 2, the results indicate that categorization tasks can serve to identify pre-experimental relations; consistent relations between stimuli were observed for different participants. Furthermore, it was observed that this task can produce unprogrammed contextual controls that interfere with categorization responses. The results of Experiment 3 confirm that the use of meaningful stimuli produces the merging of experimental and pre-experimental classes, and that teaching tasks involving arbitrary relations between stimuli can affect participants' previously learned categories. Experiment 4 showed that systematic alternation between teaching and testing tasks can facilitate the learning and derivation of arbitrary relations between stimuli, compared to procedures requiring strict accuracy criteria before testing, and highlights the importance of a consistent baseline as a criterion for the emergence of relations. This investigation initiated a new line of research on the formation of equivalence classes under contingencies with varying degrees of baseline accuracy before the presentation of derived relation tests. Collectively, the studies deepen the discussion on the use of meaningful stimuli in teaching and the derivation of new arbitrary relations between stimuli.
Investigations on meaningful stimuli and the formation of equivalence classes among stimuli
Keywords: Relações arbitrárias; Significado; Equivalência de estímulos; Categorização; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO